Rederijkers, Kannenkijkers: Drinking and Drunkenness in the Sixteenth and Seventeenth-Century Low Countries - Anne-Laure Van Bruaene; Sarah Van Bouchaute (Early Modern Low Countries, 2017)
This article discusses drinking practices and conceptions of drunkenness in the sixteenth- and seventeenth-century Low Countries from the perspective of the rederijkers or guildsmen who would regularly gather together to practice the vernacular art of rhetoric. The essay surveys the regulations and accounts of the chambers of rhetoric in which these gatherings took place, as well as the literary texts the rederijkers produced (including poetry, songs and theatre plays). It also examines the intersections with contemporary genre painting. The central argument of this paper is that drinking, and even drunkenness, was an essential aspect of rederijker culture and the urban middling groups represented by this culture. This argument nuances the influential thesis of the pervasiveness of a Dutch burgermoraal or bourgeois morality. Even though they created comical caricatures of drunkards, rederijkers indulged in heavy drinking themselves. These guildsmen were well aware of the need for moderation, but their regulations and literary texts go beyond moral didacticism and often reveal double layers and self-parody.